2008
DOI: 10.1109/icpr.2008.4761148
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the recognition of a wide Arabic handwritten word lexicon

Abstract: This paper introduces a novel approach for the recognition of a wide vocabulary of Arabic handwritten words. Note that there is an essential difference between the global and analytic approaches in pattern recognition. While the global approach is limited to reduced vocabulary, the analytic approach succeeds to recognize a wide vocabulary but meets the problems of word segmentation especially for Arabic. Combining the neural approach with some linguistic characteristics of the Arabic, it is expected that we be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…This work shows that giving slightly higher weight to linguistic information offers not only better results, but also solutions to handle wider vocabulary. In comparison with our previous work [2], the taking into account of the above improvements (letters order, "sister letters", neurons splitting up, networks supervising and ambiguity solving) has proven to significantly help the model reach its classification goal. Results are provided and show that, even without considering yet the suggested improvement proper to the recognition stage (perceptive cycles and linguistic constraints), our approach always produces higher success rates than the current approaches with regard to the vocabulary size as illustrated in table 1.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This work shows that giving slightly higher weight to linguistic information offers not only better results, but also solutions to handle wider vocabulary. In comparison with our previous work [2], the taking into account of the above improvements (letters order, "sister letters", neurons splitting up, networks supervising and ambiguity solving) has proven to significantly help the model reach its classification goal. Results are provided and show that, even without considering yet the suggested improvement proper to the recognition stage (perceptive cycles and linguistic constraints), our approach always produces higher success rates than the current approaches with regard to the vocabulary size as illustrated in table 1.…”
Section: Discussionmentioning
confidence: 89%
“…In [2], we proposed an approach for the recognition of a wide Arabic canonical vocabulary. The idea is to integrate linguistic knowledge to a perceptive model by the use of transparent neural networks (TNN), having as input global primitives of words.…”
Section: Neural-linguistic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, from the root K -T -B ( ), lemmas are formed using Arabic schemes, e.g., (" ", "a library"), and by adding the prefix " " and the suffix " " to the lemma, we obtain the word (" ", "and in their library") [8][9][10]. In our study of Arabic user attitudes toward search engines [11], we found that query paraphrasing is a common search strategy.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, word morphological analysis and factorization seem to be one solution. Actually, in this context, we have already proposed, in a previous work (Ben et al, 2008); (Ben et al, 2010), a classifiers combination based approach that uses linguistic knowledge to simplify the enormous number of Arabic words. The simplification was based on word factorization in morphological entities (root, schemes and conjugation) since we deal with decomposable words.…”
Section: Introductionmentioning
confidence: 99%